Human Factors that Derail Extension Services Delivery in Developing Countries: Implications for Policy - Ajani, EN; Onwubuya, EA (International Journal of Agricultural Research, Innovation and Technology, 2013)
The paper examines human factors derailing extension services delivery in developing countries. Poor management of rewards and incentives; quality of work life; poor assessment system; limited quality of human resource; inadequate extension support training materials; inconsistencies of government programmes; inadequate staff training and poor extension programme evaluation were viewed as major constraints. Considering the role of extension to agricultural development, the paper recommends that efforts should be made by the various stakeholders in agricultural extension services to improve the capability of human resources involved in extension services and highlights the need for government agricultural programmes to be consistent to enable the beneficiaries of such programmes derive the benefits that will boost productivity in agriculture. DOI: http://dx.doi.org/10.3329/ijarit.v2i2.14015 Int. J. Agril. Res. Innov. & Tech. 2 (2): 54-57, December, 2012